The Wall Street journal complete small business guidebook - DeBaise, Colleen (New York : Three Rivers Press, 2009)
The country's most-trusted source for financial information offers business and lifestyle strategies that can help turn small-business dreams into sustainable successes.
Starting and funding your own business. So you think you want to be a small business owner? ; Writing a business plan ; The lean years ; Once your feet are wet ; Finding an angel ; Seeking venture capital ; Special programs for women and minorities ; Organic growth strategies ; Handling your company's finances -- the mechanics of running a business. Management basics ; Legal structures ; Technology ; Marketing ; Hiring employees ; Benefits : health care and retirement ; Exit strategies -- Balancing work and life. Managing stress ; The end of paid leave ; Working from home, or, Living in your office ; Judging the demands of family and work -- Appendix 1. Jolly's Java business plan -- Appendix 2. Better Business Bureau worksheets for estimating start-up costs.
Includes index.
Keywords: Small business; Small business -- Finance; Entrepreneurship